An uncertain future : voices of a French Jewish community, 1940-2012 : the Jews of Dijon - Weiner, Robert I.; Sharpless, Richard E. (Toronto : University of Toronto Press, 2012)
"This contemporary oral history, based on interviews and recorded observations made over an eighteen-year period, tells the compelling story of the small Jewish community of Dijon, France, and how it has evolved over time in response to both internal and external challenges.
The twenty-four interviews included in the book provide first-hand narratives on compelling issues such as the lingering impact of the Holocaust, anti-Israeli sentiments, and intermarriage within and outside the community. Interviewees include the community's rabbi, the president of the community's synagogue, the Jewish deputy mayor, Holocaust survivors and their children, as well as representative members from the Lubavitcher (ultra-Orthodox) community.
The authors provide introductions to the interviews as well as a detailed history of the Jewish community in Dijon. The book includes a chronology, a glossary, a detailed map of Dijon, and photos of many of the interviewees."--pub. desc.
Rabbi Simon Sibony -- Cathie Bussidan -- Israel "Izy" Cemachovic -- Albert Huberfeld -- Francoise Tenenbaum -- Bebe Edelman -- Marcelle David -- Nadia Kaluski -- Deborah Bensoussan -- Luna Cemachovic -- Alain Danino -- Malou Dressler -- Annie Edelman and Maurice "Gislain" Bensoussan -- Alain Grynberg -- Elie Sadigh -- Jennifer Taieb -- Haim Slonim and Hannah Slonim -- David Laufer Marcel and Leah Tobis -- Jean-David and Arielle Attal -- Alex Miles -- Babette Miles.
Includes bibliographical references (p. 315-328) and index.
Issued also in electronic formats.
Keywords: Jews -- France -- Dijon -- History -- 20th century; Jews -- France -- Dijon -- History -- 21st century; Jews -- France -- Dijon -- Biography; Dijon (France) -- Ethnic relations